Manual de fotoeducação para prevenção do câncer de pele - Almeida, Augusto Cesar De Melo [UNIFESP] (2020)
Introduction: Skin cancer is the most common neoplasm in Brazil and ultraviolet radiation from the sun is the main causative agent. The large number of cases of skin cancer, possible mutilation and the high cost of treatment, make this an important public health problem. The need for a personalized approach to photoeducation is emphasized, especially among risk groups, regarding photoprotection and photoexposure. Objective: To develop and validate a photo-education manual, aimed at workers who exercise their activities outdoors, as a preventive measure against skin cancer. Methods: Descriptive study, approved by the research ethics committee of Unifesp, with bibliographic survey, search for precedence, selection of the target audience for development and validation with expert judges by the Delphi Technique calculating the Content Validation Index (CVI) and evaluation by target audience. Results: The “Photo-education Manual for Skin Cancer Prevention” was developed with 24 pages, 13 chapters and registered in the ISBN. The manual was validated by specialists in two cycles using the Delphi Technique. In the first cycle, the global CVI was 0.93, in the second, after adjustments suggested by the judges, the global CVI was 0.99. Both cycles for each item were greater than 0.78, reaching the goal for validation by the experts. The agreement between the evaluators of the target audience was 100%. Conclusion: A photoeducation manual was developed and validated, aimed at workers who perform their activities outdoors, as a preventive measure against skin cancer.